Crying Sun (Memorial ; Witness, 2007)
Verzio FF Submission Chechnya has been deeply scarred by years of fighting between separatists and Russian federal forces. "Crying Sun" is the story of Zumsoy, a village torn apart by war. It gives voice to the people who are struggling to preserve their identity amidst violence and suffering. The film calls on local and federal authorities to investigate human rights abuses and help villagers return to their ancestral homes and rebuild their lives.